Analisis Praanggapan Acara Lapor Pak Dalam Tayangan Akun Youtube @7 Comedy Serta Manfaatnya Sebagai Bahan Ajar Menulis Teks Anekdot Di SMA - Selsia, Niken Widya; Pratiwi, Wienike Dinar; Triyadi, Slamet (Peneliti.net, 2024)
This research draws problems in a communication activity in the community indirectly on the YouTube application media. The use of language contained in YouTube media varies, starting from the use of formal language and free (informal) language. In the free use of language, there are many other understandings in it. So that this research discusses the analysis of presuppositions with the subject of a joke show called Lapor Pak which is on the @7 Comedy YouTube channel and the object in the form of presuppositional speech contained in the Lapor Pak program entitled [Full] Interrogation of Najwa Shihab, Tense and Makes My Heartbeat! | Report Sir (29/06/22), [Full] Ayu Hastari Magang, Angelina Sondakh is roasted!| Report sir! (03/08/22). The purpose of this study is to describe the form, type, and meaning of presuppositions contained in the Lapor Pak YouTube channel @ 7 Comedy. This study uses a pragmatic study approach and George Yule's theory. The research was carried out using a qualitative method which was described descriptively with a speaking technique free of engagement. The results of the analysis of the data obtained on the two research objects did not show 0 presupposition results with a total of 270 utterances. The dominating presuppositions are structural presuppositions with 73 utterances and 6 other types of presuppositions, existential presuppositions, active presuppositions, lexical presuppositions, structural presuppositions, non-active presuppositions, and counterfactual presuppositions. The data obtained in the utterances are relevant to anecdotal text teaching materials on listening and writing skills.